A Linguistic Study: Satire in Malam Baretong Ceremony of Minangkabau Pariaman Wedding Tradition - Gultom, Johannes Jefria; Isnaeni, Diah Mutiara; Ginting, Hawai Apriani Br; Bahri, Syamsul (RIRAI Publisher, 2025)
ABSTRACT Satire in Malam Baretong event within the Minangkabau Pariaman wedding tradition holds profound philosophical meaning and serves as an effective tool for social control. It does not only serve as a critique but also as a tool to teach customary values, strengthen cultural identity, and maintain social balance. This applies to the Pariaman community, especially the younger generation whose understanding of Minangkabau cultural values is beginning to fade away. The purpose of this research is to understand and gain a better understanding of how satire is used in Malam Baretong event within the Minangkabau Pariaman wedding tradition. In this study, a descriptive qualitative approach is used to examine how various types of satire are clearly depicted in the Malam Baretong tradition of Minangkabau Pariaman weddings. In addition to direct observation and video recordings of Malam Baretong traditional wedding ceremony, data were also collected from books and YouTube videos containing information about the language and cultural customs of the Minangkabau Pariaman regarding Malam Baretong traditional wedding ceremony, as well as interviews with three community leaders of Pariaman to confirm the data. The findings of this research are as follows: Irony=17 (39.5%), Cynicism=9 (20.9%), Sarcasm=4 (9.3%), Antiphrasis=6 (13.9%), Innuendo=7 (16.2%). The type of satire most frequently found is Irony=17 (39.5%), indicating that the use of ironic remarks during the Malam Baretong traditional wedding ceremony of the Minangkabau Pariaman is more subtle and polite, reflecting a sense of humor in familiarity and kinship. Sarcasm=4 (9.3%) is the least frequently found because it is rarely encountered in the speech of the Minangkabau Pariaman community, especially during traditional wedding ceremonies.